Strike Activity and Wildcat Strikes in British Columbia : 1945-1975 - Fisher, E. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
This paper extends and updates the research of Professor Jamieson on strike activity in British Columbia for the period 1945-1975.